2013
DOI: 10.4271/2013-01-1665
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Engine Control Authority on HCCI Combustion as the High Load Limit is Approached

Abstract: In this study the authority of the available engine controls are characterized as the high load limit of homogeneous charge compression ignition (HCCI) combustion is approached. A boosted single-cylinder research engine is used and is equipped with direct injection (DI) fueling, a laboratory air handling system, and a hydraulic valve actuation (HVA) valve train to enable negative valve overlap (NVO) breathing. Results presented include engine loads from 350 to 650 kPa IMEP net and manifold pressure from 98 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Equation (11) gives the PPRR for point n. In this study, the data acquisition CA resolution and u(n) À u(n À 1) were 0.2°CA for the diesel engine and 0.5°CA for the gasoline engine (discussed in section ''Results'')…”
Section: Comparison With Microphone Data-pprr Calculation Methods Invmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (11) gives the PPRR for point n. In this study, the data acquisition CA resolution and u(n) À u(n À 1) were 0.2°CA for the diesel engine and 0.5°CA for the gasoline engine (discussed in section ''Results'')…”
Section: Comparison With Microphone Data-pprr Calculation Methods Invmentioning
confidence: 99%
“…Recent research has shown a lack of correlation between the three metrics discussed above. Szybist et al 11 demonstrated that RI and PPRR under-predict noise compared to AVL noise meter at boosted conditions. Dernotte et al 12 investigated the effect of intake pressure on noise and RI and demonstrated that increasing intake pressure would cause a noticeable decrease in RI at a fixed noise level.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a high boost pressure benefits HCCI-like LTC [9]. The effect of boost pressure was studied based on the baseline case.…”
Section: Fig 6 E Ffec T O F IV C P Re S S U Re a N D E G R On R C C mentioning
confidence: 99%
“…The use of cooled EGR at high load allows the intake pressure to be increased without having to decrease the intake temperatures below ambient, while still maintaining sufficiently delayed com bustion timings [8]. Szybist et al [9] also found that in order to reach higher load, it is necessary to increase the boost pressure and EGR while reducing NVO duration. The engine was equipped with DI fuelling and gasoline fuel containing nominally 10% etha nol (E10) was used.…”
Section: Introductionmentioning
confidence: 96%
“…It is well known that diesel engines require complex and expensive lean exhaust afertreatment systems for NOx and PM emissions control [14][15][16]. To address aftertreatment costs, studies are exploring innovative combustion strategies which enable higher fuel efficiencies than diesel engines while simultaneously lowering engine-out emissions to reduce aftertreatment costs [17][18][19][20]. Such novel combustion modes usually involve flameless or staged fuel combustion and are known as low-temperature combustion (LTC).…”
Section: Introductionmentioning
confidence: 99%